1991
DOI: 10.1071/pp9910037
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Nutrition, Growth and Gas Exchange in Eucalyptus globulus Labill. Seedling

Abstract: Potted Eucalyptus globulus Labill. seedlings were grown in sand with added inorganic nutrients. Three treatments were applied: (1) inorganic nitrogen was added regulary (N2), (2) in a small initial quantity only (N1) and (3) after a period of N deficiency (N3); other nutrients were supplied regularly. Biomass increment, foliar nutrient concentrations and gas exchange of leaves were measured. Carbon assimilation, N uptake, growth, and leaf production and expansion were all greater at higher N. Partitioning of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
2
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 0 publications
6
24
2
4
Order By: Relevance
“…In general P-fertilization ameliorated leaf nutrient status and presumably photosynthetic capacity (Kirschbaum and Tompkins, 1990;Kirschbaum et al, 1992;Sheriff and Nambiar, 1991). Our results show that P-fertilization improved leaf nutrient status more than N-fertilization, which can explain the higher effect on growth of P-fertilization.…”
Section: Nutrient Concentrationmentioning
confidence: 55%
“…In general P-fertilization ameliorated leaf nutrient status and presumably photosynthetic capacity (Kirschbaum and Tompkins, 1990;Kirschbaum et al, 1992;Sheriff and Nambiar, 1991). Our results show that P-fertilization improved leaf nutrient status more than N-fertilization, which can explain the higher effect on growth of P-fertilization.…”
Section: Nutrient Concentrationmentioning
confidence: 55%
“…The effects of atmospheric and soil water stress on photosynthesis are primarily caused by changes in g s in response to D and c, respectively (Leuning, 1990). Positive associations between A max and leaf nitrogen concentration in E. globulus (Sheriff and Nambiar, 1991;Pereira et al, 1994) and E. grandis (Leuning et al, 1991a), and leaf phosphorus concentration in E. grandis (Kirschbaum and Tompkins, 1990) have been found for Eucalyptus species. In an investigation using E. globulus seedlings, Sheriff and Nambiar (1991) observed a linear relationship between A max and leaf nitrogen concentration when A max was <12.2 mmol m À2 s À1 .…”
Section: Photosynthesismentioning
confidence: 89%
“…Roberts and Rosier (1993) adopted a single-layer model because of the lack of changes in values of g s , temperature and vapour pressure deficit with depth in the canopies. Transpiration was very sensitive to the value of L and largely Table 6 Values of maximum stomatal conductance (g smax ) maximum photosynthesis rates (A max ) maximum rates of carboxylation activity (V cmax ) and rates of electron transport at saturating irradiance (J max ) for selected Eucalyptus species This Table is compiled from data published by Grassi et al (2002), Kirschbaum and Farquhar (1984), Kirschbaum and Tompkins (1990), Kuppers et al (1987), Dye and Olbrich (1993), Roberts and Rosier (1993), Sheriff and Nambiar (1991), Sheriff (1992), Wullschleger (1993), Eamus et al (1995), David et al (1997), Eamus and Cole (1997), Myers et al (1997), Kallarackal and Somen (1997), Mielke et al (1999), White et al (1999White et al ( , 2000, James and Bell (2000), Clearwater and Meinzer (2001), Close and Beadle (2003). insensitive to changes in available energy, temperature and g b .…”
Section: Transpirationmentioning
confidence: 99%
“…However, they also found that A. melanoxylon had a negative influence on E. pauciflora foliar N, Rubisco and pigment concentrations, and concluded that the facilitative influence is clearly species specific, with A. melanoxylon characteristic of a later successional stage. Experiments in fertiliser trials have also shown positive relationships between N a and A max , V cmax or J max (Leuning et al 1991;Sheriff and Nambiar 1991;Pereira et al 1992;Turnbull et al 2007) although others have found no relationships suggesting that N a was in excess of photosynthetic requirements and that A max was limited by other factors (Warren et al 2000;Close et al 2004). The improved foliar nutrition of A. mearnsii in mixtures may be a result of a reduction in competition for those nutrients by E. globulus compared to other A. mearnsii.…”
Section: Foliar Nutrition and Photosynthesismentioning
confidence: 90%
“…Turnbull et al (2007) also found that the application of N, P and K fertiliser increased g s of E. globulus trees in monocultures, perhaps by ameliorating K limitations on stomatal functioning. However, while a positive and linear correlation was found between g s and N a in an N fertiliser experiment with E. globulus (Sheriff and Nambiar 1991), N fertiliser did not influence g s of E. grandis, where the effect of fertiliser on A max was biochemical (higher V cmax and J max ) (Grassi et al 2002).…”
Section: Mixture Effects On Growth and Photosynthesismentioning
confidence: 90%